The disturbed state of the Russian realm - Bussow, Conrad, -1617 (McGill-Queen's University Press, 1994)
Conrad Bussow (1552-1617), a soldier of fortune from Lower Saxony, spent most of his career in foreign service. He arrived in Russia in 1600 and spent the next eleven years serving under a variety of rulers and rebel leaders. He witnessed many of the sensational events of that period: the triumph of the first False Dmitry and his subsequent overthrow, the Bolotnikov rebellion (his description is the most detailed provided by any contemporary observer), the civil strife and foreign intervention which bedeviled the reign of Tsar Vasily Shuisky; the Polish occupation of the Kremlin, and the beginning of the Russian struggle for national liberation. Bussow had all the instincts of an investigative reporter - most of the events he recounts are from first-hand experience - and he interviewed many of the key players. Although at one time a fairly prosperous landowner, Bussow was eventually reduced to living on the charity of his wife's relatives. He tried to recoup his fortunes by becoming an author, but died before his ambition could be realized. His authorship of this work remained largely unknown until the mid-1800s. This is the first English translation of the unabridged text of Bussow's chronicle. It is based on careful examination not only of various printed versions in early modern High German but also of several of the original manuscripts in the Herzog August Library, Wolfenbuttel. Complemented by an illuminating commentary by Edward Orchard, it will be of particular interest to those concerned with Russian and European history and the evolution of the Russian "spirit."